Research Advances in Multi-Omics on the Traditional Chinese Herb Dendrobium officinale - Wang, Yue; Tong, Yan; Adejobi, Oluwaniyi Isaiah; Wang, Yuhua; Liu, Aizhong (Frontiers in Plant Science, 2022)
Dendrobium officinale Kimura et Migo is an important epiphytic plant, belonging to the Orchidaceae family. There are various bioactive components in D. officinale plants, mainly including polysaccharides, alkaloids and phenolic compounds. These compounds have been demonstrated to possess multiple functions, such as anti-oxidation, immune regulation and anti-cancer. Due to serious shortages of wild resources, deterioration of cultivated germplasm and the unstable quality of D. officinale, the study has been focused on the biosynthetic pathway and regulation mechanisms of bioactive compounds. In recent years, with rapid developments in detection technologies and analysis tools, omics research including genomics, transcriptomics, proteomics and metabolomics have all been widely applied in various medicinal plants, including D. officinale. Many important advances have been achieved in D. officinale research, such as chromosome-level reference genome assembly and the identification of key genes involved in the biosynthesis of active components. In this review, we summarize the latest research advances in D. officinale based on multiple omics studies. At the same time, we discuss limitations of the current research. Finally, we put forward prospective topics in need of further study on D. officinale.